Loss of Microbial Niche Specificity Between the Upper and Lower Airways in Patients With Cystic Fibrosis. (3rd October 2018) - Pletcher, Steven D.; Goldberg, Andrew N.; Cope, Emily K.
Abstract : Objectives/Hypothesis: To determine the relationship between mucosal‐associated sinus and bronchial microbiota in cystic fibrosis (CF) patients compared to non‐CF patients with chronic rhinosinusitis (CRS). Study Design: Case series. Methods: We examined the microbial composition of 52 paired sinus and bronchial brushings from 26 patients with CRS. Paired airway samples from nine subjects with CF were compared with samples from 17 non–CF‐CRS disease control patients. The Illumina MiSeq platform was used to sequence the V4 region of the 16S rRNA gene. Sequences were analyzed using QIIME 1.9.0. Results: CF patients demonstrate increased severity of sinus inflammation (Lund‐Mackay score 16.3 vs. 12.4, P  = .023) and diminished diversity of microbial communities in both the sinuses (Shannon diversity 0.98 vs. 3.3, P  = .009) and lungs (Shannon diversity 2.2 vs. 4.0, P  = .042) relative to non–CF‐CRS. Non–CF‐CRS sinus and lung microbiota were distinct and clustered by niche (sinus vs. lung, P  = .004). However, CF airway microbiota demonstrated a loss of niche specificity (sinus vs. lung, P  = .492). Two CF patients underwent lung transplantation at 4.5 and 9 months prior to sampling. Sinus and lung samples from these two patients demonstrated distinct microbial communities. Conclusions: Patients with CF undergoing surgery for CRS exhibit substantial bacterial community collapse in the sinuses and a loss of niche specificity between the upper and lower airways compared to non‐CF patients with CRS. These results extend previous studies elucidating the lower airway microbiome in cystic fibrosis and provide support for the concept of microbial translocation in the cystic fibrosis airways. Level of Evidence: 4 Laryngoscope, 129:544–550, 2019